BASICS OF THE METHODOLOGY FOR ASSESSING THE RESILIENCE OF THE TRANSPORT INFRASTRUCTURE (Perner's Contacts, 2021)
Assessment of the resilience of transport infrastructure is an important part of risk assessment and continuous improvement of the safety of the evaluated element. Resilience is the ability of an element to resist, absorb and adapt to the effects of adverse events. There are many approaches to resilience evaluation. As in any field, it is appropriate to develop a uniform resilience evaluation methodology. Such a methodology can unify input and output information and facilitate the assessment of the resilience level itself. Transport and transport infrastructure are complicated technical systems that require a specific approach. The aim of the article is to analyze the currently available methodologies used in the assessment of resilience and to present a proposal for a uniform methodology specific for the evaluation of the resilience of transport infrastructure.
Keywords: methodology; resilience; transport infrastructure